2020
DOI: 10.1136/bmjopen-2019-035947
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Interventions for Diabetic Foot Ulcer Treatment Trial (MIDFUT): study protocol for a randomised controlled trial

Abstract: IntroductionDiabetes affects more than 425 million people worldwide with a lifetime risk of diabetic foot ulcer (DFU) of up to 25%. Management includes wound debridement, wound dressings, offloading, treatment of infection and ischaemia, optimising glycaemic control; use of advanced adjuvant therapies is limited by high cost and lack of robust evidence.Methods and analysisA multicentre, seamless phase II/III, open, parallel group, multi-arm multi-stage randomised controlled trial in patients with a hard-to-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Participants indicated that funders often ask for blinded trials but not blinded statisticians. Although there are examples for trials where funders paid for multiple statisticians [ 16 , 17 ], the perception and indeed experience of some participants was that funders pushed back on applications including funding for multiple statisticians. “…funders don’t want to pay for multiple statisticians, as we know.…”
Section: Resultsmentioning
confidence: 99%
“…Participants indicated that funders often ask for blinded trials but not blinded statisticians. Although there are examples for trials where funders paid for multiple statisticians [ 16 , 17 ], the perception and indeed experience of some participants was that funders pushed back on applications including funding for multiple statisticians. “…funders don’t want to pay for multiple statisticians, as we know.…”
Section: Resultsmentioning
confidence: 99%
“…This may be because diabetic foot complications are different from most diseases, and the treatment requires the involvement of multiple specialties. Diseases treated by multidisciplinary collaboration are likely to become more common in the future (37). Therefore, further research on the needs of patients with this disease can provide helpful insight regarding modern medical treatment-oriented by patient needs and interdisciplinary collaborative treatment models.…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of the remaining 128 articles were assessed. The following articles were excluded due to: reviews (55); study about nonadjuvant therapy (18); study on fresh fracture (10); conference abstract (6); duplicate publication (2); study about same therapeutic strategies (2); no predetermined outcomes reported (2); comments (2); study on children congenital anomaly (1). Finally, thirty studies were included in the analysis (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%